Comparação de arranjos de coletores de calha parabólica com relação ao intervalo de rastreamento e ao tubo absorvedor - Watanabe, Thiago Taketaro Guilherme (2017)
The use of renewable energy is growing every day as an alternative to fossil fuel technology. This is mainly the search for less polluting equipment that do not harm the environment. solar energy is known as a good alternative due to its wide availability and energy potential that can be used in various ways, but the best known are the photovoltaic and solar thermal. The first one is the sun's energy conversion into electricity and the other uses heat to warm fluids that can also generate electricity. The research and the use of parabolic solar collectors have been growing because of the ability to heat fluids to high temperatures in a relatively small area. Parabolic solar collectors consist of a base which supports a surface that reflects the sun's rays on an absorber pipe through which passes water. In the solar Energy and Natural Gas Laboratory two solar collectors of small parabolic were deployed and tests were conducted to improve the arrangements in order to increase the thermal efficiency of the collectors. Finally, an automation has been made to prevent the collectors to be manually rotated, which expends time and effort. With a step motor and a control we used a low-cost system with Arduino and LDRs. It was also made a design of photovoltaic panels in order to make the system hybrid and independent of the electric grid. At the end of the tests performed, it was found that the best was the one with tracking every 5 minutes, because adjusting every 1 minute the system activates without necessarily moving since there was not time to make a difference in the LDRs; and with a tracking time of 15 minutes there was power lost, since the sun rays are dislodged from the focus not hitting the absorber.